Evil and Creation: historical and Constructive Essays in Christian Dogmatics - Araujo, Glauber Souza (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2023)
Resenha do livro LUY, David; LEVERING, Matthew; KALANTZIS, George (orgs.). Evil and Creation: historical and Constructive Essays in Christian Dogmatics. Bellingham, WA: Lexham Press, 2020. 336 p. (Studies in Historical and Systematic Theology) ISBN 9781683594345.